Cost analysis of prevalent diseases in two Peruvian Ministry of Health pediatric intensive care units - Alvarado-Jaramillo, Julio César (2011)
Introduction: With current subsidized Peruvian government Integral Health Insurance and private specific insurance for certain lesions (compulsory traffic accidents insurance), health care providers look for cost reduction and recovery. This paper seeks to be a health economic evaluation tool to facilitate financial decision making. Objectives: To determine costs of most prevalent diseases at two pediatric hospitals. Design: Absorption costing. Settings: Hospital Nacional Dos de Mayo’s Neonatal Intensive Care Unit (NICU) and Hospital de Emergencias Pediatricas’ Pediatric Intensive Therapy Unit (PITU), Lima, Peru. Material: Clinical charts and reported costs. Interventions: Revision of 100 randomly obtained clinical charts from both institutions (50 from each). Money amounts corresponding to administrative organic units included in indirect costs were not comprised. Main outcome measures: Costs of most frequent diseases. Results: During the first semester 2004 most frequent disease at Hospital Nacional Dos de Mayo NICU was neonatal sepsis; average treatment cost was S/. 3 231.34 nuevos soles and average stay length was 11 days. In regards to Hospital de Emergencias Pediatricas PITU we included all pathologies requiring mechanical ventilation; average unit price was S/. 5 076.52 nuevos soles with 8 days average stay length. Conclusions: Average cost of most frequent pathologies at pediatric intensive care units studied varied from S/. 3 231,34 to S/. 5 076,52 nuevos soles, with average stay length 8 to 11 days.